Bridging micro and macroevolution: insights from chromosomal dynamics in plants - Benítez-Benítez, Carmen; Mohan, Ashwini V.; Sánchez-Villegas, Rogelio; Gómez-Ramos, Inés; Valdés-Florido, Ana; Lucek, Kay; Slovák, Marek; Kolář, Filip; Leitch, Ilia J.; Luceño, Modesto; Larridon, Isabel; Carta, Angelino; et al. (Frontiers in Plant Science, 2025)
Understanding the relationship between macro- and microevolutionary processes and their delimitation remains a challenge. This review focuses on the role of chromosomal rearrangements in plant population differentiation and lineage diversification resulting in speciation, helping bridge the gap between macro- and microevolution through chromosomal evolution. We focus on angiosperms, a group that comprises the majority of extant plant species diversity and exhibits the largest chromosomal and genomic variations. Here, we address the following questions: Are macroevolutionary patterns of chromosome evolution the result of accumulated microevolutionary changes, or do chromosomal dynamics drive larger shifts along the speciation continuum? At the macroevolutionary level, we investigated the association between karyotype diversity and diversification rates using evidence from comparative genomics, chromosomal evolution modelling across phylogenies, and the association with several traits across different angiosperm lineages. At the microevolutionary level, we explore if different karyotypes are linked to morphological changes and population genetic differentiation in the same lineages. Polyploidy (autopolyploidy and allopolyploidy) and dysploidy are known drivers of speciation, with karyotypic differences often leading to reproductive barriers. We found that dysploidy, involving gains and losses of single chromosomes with no significant change in overall content of the genome, appears to be relatively more frequent and persistent across macroevolutionary histories than polyploidy. Additionally, chromosomal rearrangements that do not entail change in chromosome number, such as insertions, deletions, inversions, and duplications of chromosome fragments, as well as translocations between chromosomes, are increasingly recognized for their role in local adaptation and speciation. We argue that there is more evidence linking chromosomal rearrangements with genetic and morphological trait differentiation at microevolutionary scales than at macroevolutionary ones. Our findings highlight the importance of selection across evolutionary scales, where certain chromosomal dynamics become fixed over macroevolutionary time. Consequently, at microevolutionary scales, chromosome rearrangements are frequent and diverse, serving as key drivers of plant diversification and adaptation by providing a pool of variation from which beneficial chromosomal changes can be selected and fixed by evolutionary forces.